A fast synchronously rotating reference frame-based voltage sag detection under practical grid voltages for voltage sag compensation systems - Y. Kumsuwan (2018)
A Fast synchronously rotating reference frame (FSRRF)-based voltage sag detection under practical grid voltages for voltage sag compensation systems is proposed in this paper. The proposed voltage sag detection is also based on abc-dq transformation as conventional synchronously rotating reference frame (CSRRF)-based voltage sag detection but adding of 2ω component eliminator (2ω component is generated by synchronously rotating reference frame-based transformation in unbalance voltage sag conditions) and dedicated band-stop filter (BSF) (to exclude the effect from harmonic voltages in practical grid voltages) then very fast voltage sag detection time under practical grid voltages condition is achieved. The computer software simulation and the experimentation are made to investigate and verify the operation of proposed voltage sag detection. The detection time of FSRRF-based voltage sag detection is around one eighth of CSRRF-based voltage sag detection in the case of single-phase voltage sag and around one fifth in the case of two-phase voltage sag. This voltage sag detection can be used in any voltage sag or interruption compensation systems to improve their performance.